2016
DOI: 10.1128/jcm.02760-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MALDI Biotyper Mycobacteria Library v3.0 for Identification of Nontuberculous Mycobacteria

Abstract: e Matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) has demonstrated its ability to promptly identify nontuberculous mycobacteria using the Mycobacteria Library v2.0. However, some species are particularly difficult to identify reliably using this database, providing a low log(score). In this study, the identification power of an updated Mycobacteria Library (v3.0) has been evaluated. Overall, 109 NTM isolates were analyzed with both databases. The v3.0 database allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 6 publications
1
48
0
Order By: Relevance
“…In recent years, the technique has also started to be implemented in mycobacterial laboratories due to substantial improvements in sample preparation and the quality of spectral databases. We confirm in this study that MALDI-TOF MS allows a very reliable distinction between M. tuberculosis and NTM species if score thresholds are lowered from Ն2.0 for routine bacterial identifications to Ն1.8 for mycobacteria (30)(31)(32). Using this cutoff value, 90.4% of the species identifications corresponded to gold-standard methods despite the presence of two MBT-ASTRA standard peaks in the mass spectra.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In recent years, the technique has also started to be implemented in mycobacterial laboratories due to substantial improvements in sample preparation and the quality of spectral databases. We confirm in this study that MALDI-TOF MS allows a very reliable distinction between M. tuberculosis and NTM species if score thresholds are lowered from Ն2.0 for routine bacterial identifications to Ն1.8 for mycobacteria (30)(31)(32). Using this cutoff value, 90.4% of the species identifications corresponded to gold-standard methods despite the presence of two MBT-ASTRA standard peaks in the mass spectra.…”
Section: Discussionsupporting
confidence: 62%
“…As it allows pathogen-specific culture and protein extraction protocols (34,35), we first optimized our in-house mycobacterial cell disruption and protein extraction protocol for MALDI-TOF MS analysis. Upon comparison of various described protocols using M. tuberculosis H37Rv cells (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), we found that in our hands, bead beating in the presence of 1.2 ml of 70% ethanol gave the best output in terms of peak intensity and identification scores (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of mycobacteria has not reached an optimal level of routine testing yet and published studies showed discrepant performances, depending on spectrometer, extraction method, algorithm, library, media, and biomass used for the assays (15)(16)(17)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). In this study, we compared two distinct databases of Vitek-MS, the Saramis v4.12 open database and the new IVD v3.0 closed database.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially evaluated with mycobacterial intact cells (9)(10)(11)(12), but several investigators worked on improving inactivation and protein extraction (13)(14)(15)(16)(17)(18)(19)(20). Most published studies assessed the performance of MALDI-TOF BioTyper (Bruker Daltonics, Bremen, Germany) (15,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Few of them evaluated Vitek MS (bioMérieux, Marcy l'Etoile, France) (16,17,20,24,25,32).…”
mentioning
confidence: 99%